Peake, Linda i Rieker, Martina (eds.) (2013). Rethinking feminist interventions into the urban - Ortiz Guitart, Anna (Documents d’Anàlisi Geogràfica, 2014)
Peake, Linda i Rieker, Martina (eds.) (2013). Rethinking feminist interventions into the urban Oxon: Routledge, 214 p. ISBN 978-0-415-51881-9